Consumer perceived ethicality of banks in the era of digitalisation: The case of Poland - Piotrowski, Dariusz (Economics and Business Review, 2022)
Ethically conducted business has a positive impact on consumer trust, satisfactionand loyalty. The aim of this paper is to identify the bank activities that customersperceive as ethical and to what extent they affect consumer perceived ethicality.The binomial logit model applied in this study demonstrates that the honesty offinancial advice, use of e-banking services and use of artificial intelligence technologyto improve the quality of banking services have a significantly positive impact on consumers’perception of banks in Poland as ethical institutions. Significant variables thatnegatively influence consumer perceived ethicality include gender, education, use offinancial advisory services, banks’ manipulation of information about financial productsand use of personal data against the will of customers.